Capstone Project Data Analytics Untuk Menigkatkan Penjualan Secara Efektif - Angelia Fortunata Arisman; Ulfa Puspa Wanti Widodo (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Amidst the fierce competition in the coffee shop industry in New York, many businesses have experienced a decline in sales, especially in certain products. This research aims to discuss the Capstone Data Analytics project to increase product sales at coffee shops in New York, focusing on the decline in sales of packaged chocolate products. Through a descriptive quantitative analysis approach, sales data from three branches of the coffee shop were evaluated to understand the factors influencing the sales decline. Findings showed that high prices and stagnant sales trends were the main causes of sales decline. Recommendations include price optimization, increased promotion, product diversification, and understanding market trends to increase sales by 2-5% in the following year.